Comparision of Surgical Outcome Between Dismembered Pyeloplasty with or Without Double J Stenting - Rafique Ahmed Sahito, Sikander-e-Azam Yousfani, Abdul Aziz Sahito , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To assess the benefit of temporary ureteral stenting with double J stent on the surgical outcome of dismembered pyeloplasty. Study Design: Prospective Comparative Study Place & Duration: Department of urology at People Medical College Hospital Nawahshah during the period of 2008 to 2010. Material & Methods: Forty consecutive patients of any age and sex having primary pelviureteric junction obstruction were admitted. All patients underwent open Anderson Hynes pyeloplasty with or without double J stent. Post-operative complications and outcomes were recorded. Results: Most of our patients were male 30 (75%) and female 10 (25%). Majority of them belonged to age group 1-5 years. Left side was affected in most 28 (70%) of the cases. We had low incidence of postoperative accepted complications p-value=0.87. Postoperative outcome was excellent in relation to urine leakage 0(0%) and hospital stay in stented group while there was no any difference regarding urinary tract infection between stented and non-stented groups. Conclusion: No significant difference in terms of resolution of hydronephrosis and postoperative complications between double J stent and without double J stent groups. However outcome was good in double J stent group in terms of no urinary leakage.